Utilizing Virtual Reality for Thaharah from the Perspective of the Mobile-Based Book Safinatun An-Najah to Enhance Learning Motivation - Achmad Munib; Mustagfirun Mustagfirun; Fandy Indra Pratama; Salman Rashid (Journal of Nonformal Education, 2025)
Education continues to evolve with the progress of the times. Based on Law Number 20 of 2003 concerning the National Education System, education is a conscious and planned effort to create a learning environment that enables students to actively develop their potential. An important aspect of Islamic religious education is the understanding of thaharah (purification), as explained in the Safinatun An-Najah book, a primary reference on the subject. Cleanliness holds a significant value in Islam, serving not only as an act of worship but also as a moral aspect that draws individuals closer to Allah. Meanwhile, the United Nations' Sustainable Development Goals (SDGs), launched in 2015, emphasize the importance of inclusive and quality education to achieve sustainable development. In line with the era of Society 5.0, technology is increasingly integrated into human life, including education, through virtual spaces and the development of learning methods based on Virtual Reality (VR). VR enhances learning experiences through immersive, interactive simulations, making it well-suited for Generation Z as the digital generation. This study examines the use of mobile-based VR in teaching thaharah from the perspective of the Safinatun An-Najah book. Mobile VR offers an interactive learning experience that can increase students' motivation in understanding thaharah. In addition to making learning more engaging, VR also helps prepare students to navigate technological advancements, thus playing a crucial role in the innovation of Islamic religious education.